Erythroxylum cuneatum enhanced receptor internalisation on morphine-desensitised neuroblastoma cells line - Suliman, Noor Azuin; Kasiraja, Veshalini; Mohd Moklas, Mohamad Aris (Walailak University, 2025)
Chronic morphine exposure disrupts receptor signalling by inhibiting receptor internalisation, leading to receptor desensitisation and reduced availability of active receptors. This process significantly contributes to morphine addiction, a condition with limited effective and accessible treatments. Current pharmacological interventions, such as methadone, face challenges including restricted availability, risk of misuse, and adverse effects, leaving a substantial treatment gap for individuals with opioid use disorder (OUD). To address this, alkaloid extract of Erythroxylum cuneatum (E. cuneatum) was investigated as a potential alternative treatment. Using the human neuroblastoma cell line (SK-N-SH), 2 experimental designs were employed: Antagonistic treatment and pre-treatment with morphine. The antagonistic design evaluated the direct interaction between morphine and E. cuneatum, while the pre-treatment model assessed its anti-addictive properties during morphine withdrawal. Methadone served as a positive control. Cytosolic protein fractions were analysed to determine the expression of G protein-coupled receptor kinase 2 (GRK2), β-arrestin 1/2, and clathrin heavy chain, essential for receptor internalisation and resensitisation. Morphine exposure significantly downregulated these proteins, indicating impaired receptor function. Treatment with the alkaloid extract of E. cuneatum reversed these effects, restoring protein levels to those comparable with methadone. These findings highlight the alkaloid extract of E. cuneatum as a promising candidate for mitigating morphine addiction by targeting the molecular mechanisms underlying receptor desensitisation and resensitisation. E. cuneatum addresses a critical gap in addiction management by providing a potential alternative therapy that overcomes some limitations of existing treatments.